1992
DOI: 10.1080/14640749208401333
|View full text |Cite
|
Sign up to set email alerts
|

Judgements of Deontic Relevance in Reasoning: A Reply to Jackson and Griggs

Abstract: Facilitation on abstract versions of the selection task can be produced by deontic content. Jackson and Griggs (1990) claimed that this finding depends on the presence of an explicit negative on the not-q card. We hypothesized that the removal of the explicit negative from this card made its deontic status ambiguous. Experiment 1 demonstrated that a not-q card presenting implicit negative is not selected, and most subjects select the only card that appears to be relevant from a deontic point of view (i.e. the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…In addition, Kroger, Cheng and Holyoak (1993) reported experiments conducted to reconcile findings reported as inconsistent with the pragmatic reasoning schema theory (see, for example, Jackson and Griggs, 1990). They suggested that the results reported by Jackson and Griggs (1990) are explained by pragmatic reasoning schemas, and their results complement findings of content effects reported by Girotto, Mazzocco and Cherubini (1992), again consistent with selective evocation of reasoning schemas.…”
supporting
confidence: 61%
“…In addition, Kroger, Cheng and Holyoak (1993) reported experiments conducted to reconcile findings reported as inconsistent with the pragmatic reasoning schema theory (see, for example, Jackson and Griggs, 1990). They suggested that the results reported by Jackson and Griggs (1990) are explained by pragmatic reasoning schemas, and their results complement findings of content effects reported by Girotto, Mazzocco and Cherubini (1992), again consistent with selective evocation of reasoning schemas.…”
supporting
confidence: 61%
“…Most recent work on the selection task has concentrated on how thematic content affects reasoning (e.g., Cheng & Holyoak, 1985Cosmides, 1989;Evans, 1989;Gigerenzer & Hug, 1992;Girotto, Mazzocco, & Cherubini, 1992;Griggs & Cox, 1982;Jackson & Griggs, 1990;Johnson-Laird & Byrne, 1991Manktelow & Over, 1987, 1990a, 1990b, 1991Rumelhart, 1980). In the selection task, this work originated in the attempt to facilitate falsificatory reasoning (Johnson-Laird, Legrenzi, & Legrenzi, 1972;Wason & Shapiro, 1971).…”
Section: Thematic Selection Taskmentioning
confidence: 99%
“…An 'only if' assertion seems to work best when its second component (B) precedes in time its first component (A) (Cheng & Holyoak, 1985;Evans & Beck, 1981;Ormerod, Manktelow, & Jones, 1993;Rips & Marcus, 1977;Thompson & Mann, 1995). 'Only if' often contains a precondition in its consequent, for example, 'you can go out to play only if you tidy your room' (Girotto, Mazzocco, & Cherubini, 1992).…”
Section: Indicative and Counterfactual 'Only If'mentioning
confidence: 99%